Children's body fatness and prevalence of obesity in relation to height for age. (January 2014) - Navti, Lifoter K.; Samani-Radia, Dimple; David McCarthy, H.
Abstract Background: Children who are taller for their age tend to have higher BMI and, as a group, a greater prevalence of overweight/obesity. Aim: To examine the relationship between height for age with three measures of adiposity. Subjects and methods: Height, weight, BMI, % body fat (%BF) (by bioimpedance) and waist circumference (WC) were measured in 2298 Caucasian children (1251 boys) aged 4–14 years. Standard deviation scores (SDS) were derived and cases divided into quartiles of height SDS. Mean BMI, %BF and WC SDSs were compared across quartiles. Prevalence of overweight/obesity, over-fat/obesity and abdominal overweight/obesity within each height for age quartile was determined. Results: Mean BMI, %BF and WC SDSs increased with increasing quartile of height SDS. Overweight/obesity, overfat/obesity and abdominal overweight/obesity prevalence increased from the first quartile (8.8–13%) to the fourth quartile (32.7–45.5%) of height SDS. A significant rising trend in mean SDSs for BMI, %BF and WC was also observed with increasing height SDS in overweight/obese children only. Conclusion: A higher prevalence of excess weight, measured by BMI SDS among children taller for their age, is replicated when using %BF and WC. Height for age measurement has potential in screening children for later risk of obesity.